BUDIDAYA BUAH-BUAHAN DI PEMATANG TAMBAK UNTUK MENINGKATKAN KESEJAHTERAAN WARGA DESA SAWOHAN - Soffil Widadah; Achmad Dhany Fachrudin (Jurnal Layanan Masyarakat (Journal of Public Services), 2019)
The purpose of KKN-PPM is to improve the welfare of the Sawohan village community in Buduran sub-district. The average size of fish ponds’ embankment in Sawohan village are 4-8 meters in wide, larger than the other. The utilization of course must consider the selection of fruit types, because there are several types of fruits that can survive in hot areas and the results are better when doused with salt water, such as golden cucumber and garbis. Tilted ponds are very beneficial as the flow of rainwater. In addition, a green house was made as an experiment to provide fruit resistance to extreme weather in ponds. In addition, an irrigation system that is sourced from river water is made with the aim of alleviating farmers. water channels as a stream of rainwater so as not to overflow. This method of implementing KKN-PPM starts with debriefing students from experienced farmers. Furthermore, the implementation and practice of planting in ponds and providing education to residents by conducting socialization and seminars. It is expected that the villagers will be motivated and willing to practice. The last hope is that the welfare of the Sawohan village community in Buduran sub-district, Sidoarjo district can be improved.